1987
DOI: 10.1159/000199408
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Somatostatin Analogue Sandostatin (SMS 201–995) on Gastrointestinal, Pancreatic and Biliary Function and Hormone Release in Normal Men

Abstract: The effect of the long-acting somatostatin analogue Sandostatin (SMS 201–995) on intestinal absorption and propagation (mouth-to-caecum transit time; MCTT), on pancreatic secretion and on gall bladder contraction after direct (secretin-pancreozymin test) and indirect stimulation (Lundh meal), and on meal-induced responses of seven gastrointestinal regulatory peptides has been investigated. In a double-blind cross-over study, 9 healthy volunteers completed two 7-day periods with subcutaneous injections of eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
2

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(100 citation statements)
references
References 22 publications
7
91
2
Order By: Relevance
“…Consequently, in the present studies we infused either palm oil or safflower oil via enteral feeding tube. Because lipid absorption from the proximal small intestine requires CCK, and somatostatin is a potent inhibitor of CCK as well as peristalsis (35), initiation of the somatostatin infusion was delayed for 120 min. This method results in an increase in plasma FFA concentration within the physiological range to levels that have previously been shown to inhibit hepatic insulin action in man (8,22).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, in the present studies we infused either palm oil or safflower oil via enteral feeding tube. Because lipid absorption from the proximal small intestine requires CCK, and somatostatin is a potent inhibitor of CCK as well as peristalsis (35), initiation of the somatostatin infusion was delayed for 120 min. This method results in an increase in plasma FFA concentration within the physiological range to levels that have previously been shown to inhibit hepatic insulin action in man (8,22).…”
Section: Discussionmentioning
confidence: 99%
“…Octreotide has been shown to have similar effects already at the low dose of 25 pg daily (19). Since IFN-a does not have this dramatic effect on hormone secretion, the rate of subjective improvement was much lower after IFN-c( than after octreotide.…”
Section: Discussionmentioning
confidence: 99%
“…Octreotide and other somatostatin analogues function to inhibit the release of endocrine and exocrine pancreatic secretions, 25 a process that effectively reduces the volume of secretions and may decrease the incidence of anastomotic leaks and pancreatic fistulas. The precise role of prophylactic octreotide remains controversial; a number of recent studies have reported inconsistent effects on postoperative complications, yet a Cochrane review on the subject concluded that perioperative complications were reduced following somatostatin analogue treatment during pancreatic resections.…”
Section: Discussionmentioning
confidence: 99%